Kajian Archetype Karya Arsitektur Bangunan Kantor - Jordy Mojo; Danang Harito Wibowo (Prodi Arsitektur Universitas Matana, 2019)
This study discusses the architectural work of an office named @Batubata, owned by the architectural firm Studio Air Putih. The object was chosen because it won two prestigious awards in the best office category and a lot of media coverage. It's just that there are no studies that discuss the office academically and in detail. So in this study review looking for the main characteristics of the Studio Air Putih office by dissecting and deciphering the building elements using the Archetype understanding of Thomas Thiis Evansen's thoughts. This study uses a descriptive qualitative approach where primary data is obtained through observation and interviews. Literature study was conducted to obtain secondary data.